Development of dormant waqf properties: application of traditional and contemporary modes of financing - Sadique, Muhammad Abdurrahman (International Islamic University Malaysia, 2010)
Maintenance of waqf assets and keeping them in a productive state is emphasized in Islamic legal literature. In addition to traditional avenues, jurists have sanctioned certain special modes for sustaining awqâf, in order to ensure their continuance. Due to the specific legal nature of waqf assets in shari‘ah, some contemporary modes of financing are not readily practicable in the context of waqf. Equity based financing modes where a joint venture is initiated with the waqf assets forming part of the joint capital are not acceptable, as such modes involve partial transfer of waqf-ownership. Decreasing partnership and other formats proposed may be used for financing some waqf projects, with due observance of shari‘ah guidelines. Due to concerns that arise in certain modes principally relating to the issue of ownership, formats based on ijârah and istisnâ' appear best suited for financing awqâf.